Pengaruh Kualitas Pelayanan, Nilai Yang Dirasakan, Dan Kepercayaan Terhadap Loyalitas Pelanggan PT. KAI Di Wilayah DAOP 8 Surabaya - Anisah Salwa Agustina; Acep Samsudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study used a quantitative approach and an associative research design to investigate the effects of service quality (X1), perceived value (X2), and trust (X3) on customer loyalty (Y) of PT. KAI in the DAOP 8 Surabaya area, both partially and simultaneously. In this research, respondents from PT. KAI clients in the DAOP 8 Surabaya region, who have used transportation services at least twice, filled out a questionnaire to contribute data. Using the Lemeshow Formula, 96 respondents were determined as representative samples. The study assessed the validity and reliability of the research instrument, with results supporting their credibility. Data analysis employed multiple linear regression, supplemented by tests for classical assumptions, F-tests, t-tests, and coefficient of determination tests. Through t-test analysis (partial test), the study revealed that while service quality (X1) doesn't significantly impact customer loyalty (Y), perceived value (X2) and trust (X3) do. The coefficient of determination, at 0.698, suggests that service quality, perceived value, and trust collectively influence customer loyalty by 69.8%, leaving 30.2% influenced by other variables beyond the model.